PROVIDING INDIRECT CORRECTIVE FEEDBACK: A Technique to Reduce Errors in Students’ Writing - Iskandar Abdul Samad; Endah Anisa Rahma; Siti Sarah Fitriani (Journal of English Education, 2016)
This experimental study aims at investigating the application of Indirect Corrective Feedback (ICF) in teaching writing recount text. The subjects of the study were tenth graders of SMAN 1 Meulaboh who are chosen randomly. The instrument used is writing tests. This study focuses on giving ICF on students’ recount writing in terms of grammatical features of the text. Accordingly, there are eight error aspects included in the analysis; these are verb, noun ending, spelling, word form, word order, pronoun, missing and unnecessary word. The findings indicate that Indirect Corrective Feedback helps students to reduce errors in eight aspects. It is shown from the decreased mean score of errors in the post-test ( = 12.17) which was lower than the mean score of errors in the pre-test (  = 27.07). Verb was the aspect reduced mostly in students’ recount texts (56) followed by word order (18), word form (16), spelling (14), pronoun (12), noun ending (11), unnecessary word (8), and missing word (3). From t-test analysis in the post-tests of both groups, this study found that t-counted was higher than t-table (1.823 ˃ 1.68). Thus, H0 was rejected. The result confirmed that Indirect Corrective Feedback can significantly improve the students’ writing achievement by the reduction of errors.